Centella asiatica extract improves senescence-associated metabolic dysfunction by targeting inflammation in adipose tissue and macrophage in obesity-induced insulin resistance mice - Barinda, Agian Jeffilano; Arozal, Wawaimuli; Dwita, Nounik Cheri; Safutra, Muhamad Sadam; Shimizu, Ippei; Hsiao, Yung Ting; Sandora, Normalina; Hakim, Rani Wardani; Khatimah, Nurul Gusti; Hardi, Harri (Frontiers in Endocrinology, 2025)
Insulin Resistance (IR) is a complication that frequently occurs in obesity. The inflammation-mediated senescence in White Adipose Tissue (WAT) is important in obesity-induced IR. Centella asiatica (CA) is a potential medicinal plant with anti-aging and anti-obesity properties. Here, we explored the effect of CA on obesity-mediated IR in mice fed with a High Fat-High Fructose (HFHF) diet and treated simultaneously with CA at 150 mg/kgBW (CA150) or 300 mg/kgBW (CA300). The total body mass and visceral WAT weight in both CA groups decreased in comparison with HFHF group alone. We demonstrated that HFHF-diet mice treated with CA300 improved insulin sensitivity and enhanced Irs-1 activation in WAT. CA300, but not CA150, prevented the senescence phenotype in WAT, represented by decreased Senescence-associated beta-galactosidase (SA-β-Gal) activity and diminished Cdkn2a and Cdkn1a expression levels at mRNA level. Mechanistically, CA300 prevented the enhancement of Il6 and Il1b mRNA expression levels and macrophage activity in the immunostaining analysis of WAT. In vitro, RAW264.7 cells stimulated with high glucose and low dose of Lipopolysaccharides (LPS) also confirmed that CA 200 μg/ml alleviated the expression levels of M1 markers such as Ccl2, Il6, Il1b, and Tnf at mRNA level. Our data indicated that CA has therapeutic potential for obesity-mediated IR by suppressing proinflammatory M1 macrophages and preventing inflammation-induced senescence in WAT.